THE CONTENDING ISSUES AND REALITIES IN NIGERIAN FEDERALISM - BENJAMIN SHAIBUME; AONDOAKAA AFONGU IORNUMBE (International Studies Journal)
The paper examines the contending issues and realities in Nigerian federalism. The paper adopted the theory of pluralism as its framework of analysis and relied on the secondary sources of data to explicate the contending issues and realities in Nigerian federalism. Before the amalgamation of Southern and Northern Protectorates in 1914, Nigeria had empires, emirates, and kingdoms that interacted diplomatically, economically, politically, socially, and culturally. These entities had unique ways of political and justice administration, conflict mediation, conciliation, and resolution processes. The amalgamation of 1914 brought new forms and patterns of exercising power, which were spelt out and entrenched in the Lugard’s Constitution of 1914. However, not all regions were represented in the Legislative Council, leading to bitter struggles and agitations towards the formation of a new government. The Richard’s Constitution in 1946 provided for regionalism, while the Macpherson’s Constitution of 1951 improved upon by introducing quasi-federalism. The Lyttleton’s Constitution of 1954 introduced federalism in Nigeria, providing greater autonomy to various regions and functional division of powers between the central and regional governments. This was the first genuine federal constitution of the country, and its adoption was externally motivated for administrative convenience of the expatriates. Nigeria’s complex diversity was a major factor that combined with other centrifugal and centripetal forces to produce a federation. The choice of a federal system of government was facilitated by the social, historical, political, and economic differences of the various groups and regions in the country. However, the legacy of colonialism continued to influence the functioning of federalism in the country. The uneven distribution of resources, power and structural imbalances, and ethnic rivalries among others have continued to challenge Nigerian federalism. The paper recommends that Nigeria's fiscal federalism should focus on revenue generation rather than distribution. Future reforms should encourage states to develop fiscal capacity, enabling them to control their own revenue. This will enhance fiscal viability and reduce oil dependency. Also, encouraging a sense of national identity and unity among the diverse ethnic nationalities in Nigeria by emphasizing shared values, history, and common goals that will bridge differences and reduce tensions.